Identification of essential genes in Coxiella burnetii. Issue 2 (1st February 2023) - Metters, Georgie; Hemsley, Claudia; Norville, Isobel; Titball, Richard
Abstract : Coxiella burnetii is an intracellular pathogen responsible for causing Q fever in humans, a disease with varied presentations ranging from a mild flu-like sickness to a debilitating illness that can result in endocarditis. The intracellular lifestyle of C. burnetii is unique, residing in an acidic phagolysosome-like compartment within host cells. An understanding of the core molecular biology of C. burnetii will greatly increase our understanding of C. burnetii growth, survival and pathogenesis. We used transposon-directed insertion site sequencing (TraDIS) to reveal C. burnetii Nine Mile Phase II genes fundamental for growth and in vitro survival. Screening a transposon library containing >10 000 unique transposon mutants revealed 512 predicted essential genes. Essential routes of synthesis were identified for the mevalonate pathway, as well as peptidoglycan and biotin synthesis. Some essential genes identified (e.g. predicted type IV secretion system effector genes) are typically considered to be associated with C. burnetii virulence, a caveat concerning the axenic media used in the study. Investigation into the conservation of the essential genes identified revealed that 78 % are conserved across all C. burnetii strains sequenced to date, which probably play critical functions. This is the first report of a whole genome transposon screen in C. burnetii that has been undertaken for the identification of essential genes.